Robots and empire - Asimov, Isaac, 1920-1992 (Robot series, 2018)
Long ago, Gladia's robots Daneel and Giskard played a vital role in opening the worlds beyond the Solar system to Settlers from Earth. Now the conscience-stricken robots are faced with an even greater challenge. Either the sacred Three Laws of Robotics are in ruins - or a new, superior Law must be established to bring peace to the galaxy. With Madam Gladia and D.G. Baley - the captain of the Settler traders and a descendant of the robots' friend Elijah Baley - Daneel and Giskard travel to the robot stronghold of Solaria ... where they uncover a sinister Spacer plot to destroy Earth itself.